PROSES EXPAND TUBE HEAT EXCHANGER ETHYLENE SUPER HEATER H072 DI PT. INTAN PRIMA KALORINDO - Eko Aprianto Nugroho; Abdul Rahman Agung Ramadhan (Jurnal Teknik dan Science, 2024)
Expand Tube is a deformation process that is carried out in a cold state, to obtain a density between the tube and the tube hole in the tube sheet. This process aims to obtain a tight/tight connection so as to prevent leaks and not be separated from the seat, while minimizing stress corrosion and cracks axially in the transition zone behind the tube sheet. heater H072: 1. Carry out the stages of expanding tube heat exchanger ethylene super heater H072. 2. Obtain data on the tube when the process of expanding the tube heat exchanger ethylene super heater H072 is carried out. 3. Know the acceptance criteria for the process of expanding tube heat exchanger ethylene super heater H072. Writing conducted research with several methods including: 1. Observation method at PT. Diamond Prima Kalorindo. 2. Interview Method. 3. Literature Study Method. PT Intan Prima Kalorindo imports materials from Korea, but these materials are controlled by PT Intan Prima Kalorindo so that these materials are in accordance with consumer demand, during the expansion process it requires 2 materials, namely Aluminum Silicon 304 Stainless Steel. The Expand process is a deformation process that is carried out in a cold state, to obtain a density between the tube and the tube hole in the tube sheet. Where the tube has reached 'plastic' while the tube sheet is still in the 'elastic' stage. This process aims to obtain a tight/tight connection so as to prevent leakage and not detach from the seat, while minimizing stress corrosion and axial cracking in the transition zone behind the tube sheet. All expand calculations refer to TEMA 10th standards (Tubular Exchanger Manufactures Associations, Inc) and API 660 (American Petroleum Institute).